Analisis Dan Pemilihan Strategi Umum Yang Digunakan Para Pedagang Kaki Lima Di Kawasan Pantai Padang - Susriyanti, Susriyanti; Yeni, Fitri; Wijaya3, Roni Andri; Diana, Yusvi (Jurnal Pengabdian Masyarakat Akademisi, 2025)
This community service activity was carried out for traders in the Padang Beach area. This service carries the title